OPTIKNEE 2022: consensus recommendations to optimise knee health after traumatic knee injury to prevent osteoarthritis. Issue 24 (15th November 2022) - Whittaker, Jackie L; Culvenor, Adam G; Juhl, Carsten Bogh; Berg, Bjørnar; Bricca, Alessio; Filbay, Stephanie Rose; Holm, Pætur; Macri, Erin; Urhausen, Anouk P; Ardern, Clare L; Bruder, Andrea M; Bullock, Garrett S; et al.
Abstract : The goal of the OPTIKNEE consensus is to improve knee and overall health, to prevent osteoarthritis (OA) after a traumatic knee injury. The consensus followed a seven-step hybrid process. Expert groups conducted 7 systematic reviews to synthesise the current evidence and inform recommendations on the burden of knee injuries; risk factors for post-traumatic knee OA; rehabilitation to prevent post-traumatic knee OA; and patient-reported outcomes, muscle function and functional performance tests to monitor people at risk of post-traumatic knee OA. Draft consensus definitions, and clinical and research recommendations were generated, iteratively refined, and discussed at 6, tri-weekly, 2-hour videoconferencing meetings. After each meeting, items were finalised before the expert group (n=36) rated the level of appropriateness for each using a 9-point Likert scale, and recorded dissenting viewpoints through an anonymous online survey. Seven definitions, and 8 clinical recommendations (who to target, what to target and when, rehabilitation approach and interventions, what outcomes to monitor and how) and 6 research recommendations (research priorities, study design considerations, what outcomes to monitor and how) were voted on. All definitions and recommendations were rated appropriate (median appropriateness scores of 7–9) except for two subcomponents of one clinical recommendation, which were rated uncertain (median appropriateness score of 4.5–5.5). Varying levels of evidence supported each recommendation. Clinicians, patients, researchers and other stakeholders may use the definitions and recommendations to advocate for, guide, develop, test and implement person-centred evidence-based rehabilitation programmes following traumatic knee injury, and facilitate data synthesis to reduce the burden of knee post-traumatic knee OA.